Intracranial gas containing epidural abscess in a closed traumatic head injury - Emmanuel Sunday; Eno-Abasi Garba Sunday (Romanian Neurosurgery)
This paper is intended as an illustrative teaching case. It presents a prototype of a closed traumatic head injury with left frontal convexity extra-axial gas containing abscess, not conclusive on CT scan. The diagnosis was, however, made intra-operatively. It went further to discuss the diagnostic challenges and management pearls of such patients and concluded with a few pertinent take-home messages.